Prevalence and factors associated with extrauterine growth restriction in premature infants - Anggareni, Komang Tria; Sidiartha, I Gusti Lanang; Artana, I Wayan Dharma; Suwarba, I Gusti Ngurah Made; Hartawan, I Nyoman Budi; Gustawan, I Wayan (Indonesian Pediatric Society, 2024)
Background Extrauterine growth restriction (EUGR) is common in preterm infants and has been shown to affect their neurodevelopment. Significant variability exists in the criteria used to define EUGR and a standard definition has not yet been established. Several factors associated with EUGR have been identified, yet EUGR remains a problem in preterm infants. There is still much to be explored regarding risk factors associated with EUGR. Objective To determine the prevalence and factors associated with EUGR in preterm infants. Methods This cross-sectional study included randomly selected premature infants (<37 weeks gestational age) who were admitted to levels II and III Neonatal Ward at Prof. Dr. I.G.N.G. Ngoerah Hospital from May 2022 to August 2023. Results Of 185 subjects, the prevalence of EUGR in preterm infants was 47% and there were significant associations between EUGR and birth weight <1500 g (PR 8.814; 95%CI: 3.943 to 19.7; P=0.000), small for gestational age/SGA (PR 28.95; 95%CI: 3.79 to 220.1; P=0.000), neonatal sepsis (PR 4.29; 95%CI: 2.21 to 8.31; P=0.000), hyaline membrane disease/HMD (PR 2.12; 95%CI: 1.16 to 3.88; P=0.021), use of respiratory support (PR 2.57; 95%CI: 1.35 to 4.92; P=0.005), initiation of enteral nutrition at >48 hours (PR 2.23; 95%CI: 1.21 to 4.09; P=0.014) and length of stay/LOS >14 days (PR 8.11; 95%CI: 4.13 to 15.9; P=0.000). Multivariate analysis revealed birth weight <1500 g (aPR 5.14; 95%CI: 1.55 to 17.06; P=0.007), SGA (aPR 24.26; 95%CI: 2.64 to 222.6; P=0.005), presence of sepsis (aPR 2.35; 95%CI: 1.00 to 5.5; P=0.049), and length of hospital stay >14 days (aPR 4.93; 95%CI: 2.15 to 11.31; P=0.000) maintained positive significant associations with EUGR. Conclusion The prevalence of EUGR in preterm infants is 47%. Birth weight <1500 g, small for gestational age, sepsis, and length of stay >14 days are associated with EUGR in preterm infants.